Evidence for Host Selectivity and Specialization by Epizoic Chelonibia Barnacles Between Hawksbill and Green Sea Turtles - Boyd, Liberty L.; Zardus, John D.; Knauer, Courtney M.; Wood, Lawrence D. (Frontiers in Ecology and Evolution, 2021)
Epibionts are organisms that utilize the exterior of other organisms as a living substratum. Many affiliate opportunistically with hosts of different species, but others specialize on particular hosts as obligate associates. We investigate a case of apparent host specificity between two barnacles that are epizoites of sea turtles and illuminate some ecological considerations that may shape their host relationships. The barnacles Chelonibia testudinaria and C. caretta, though roughly similar in appearance, are separable by distinctions in morphology, genotype, and lifestyle. However, though each is known to colonize both green (Chelonia mydas) and hawksbill (Eretmochelys imbricata) turtles, C. testudinaria is >5 times more common on greens, while C. caretta is >300 times more common on hawksbill. Two competing explanations for this asymmetry in barnacle incidence are either that the species' larvae are spatially segregated in mutually exclusive host-encounter zones or their distributions overlap and the larvae behaviorally select their hosts from a common pool. We indirectly tested the latter by documenting the occurrence of adults of both barnacle species in two locations (SE Florida and Nose Be, Madagascar) where both turtle species co-mingle. For green and hawksbill turtles in both locations (Florida: n=32 and n=275, respectively; Madagascar: n=32 and n=125, respectively), we found that C. testudinaria occurred on green turtles only (percent occurrence - FL: 38.1%; MD: 6.3%), whereas the barnacle C. caretta was exclusively found on hawksbill turtles ( FL: 82.2%; MD: 27.5%). These results support the hypothesis that the larvae of these barnacles differentially select host species from a shared supply. Physio-biochemical differences in host shell material, conspecific chemical cues, external microbial biofilms, and other surface signals may be salient factors in larval selectivity. Alternatively, barnacle presence may vary by host micro-environment. Dissimilarities in scute structure and shell growth between hawksbill and green turtles may promote critical differences in attachment modes observed between these barnacles. In understanding the co-evolution of barnacles and hosts its key to consider the ecologies of both hosts and epibionts in interpreting associations of chance, choice, and dependence. Further studies are necessary to investigate the population status and settlement spectrum of barnacles inhabiting sea turtles.